AN ANALYSIS OF TEACHERS' STRATEGIES IN IMPLEMENTING STORYTELLING TECHNIQUE FOR ENGLISH LEARNING AT MAN 2 MODEL MEDAN - Triana, Neni; Nst, Asrindah (Jurnal Warta Dharmawangsa, 2025)
This reserach aims to analyze the strategies used by English teachers in implementing storytelling techniques in English learning at State Islamic Senior High School (MAN) 2 Model Medan. The background of this study is based on the low communicative ability of students caused by teaching methods that are still conventional and teacher-centered. Storytelling techniques are seen as an innovative approach that can improve students' language skills through communicative, expressive, and meaningful contexts. This study uses a descriptive qualitative approach with four English teachers at MAN 2 Model Medan who have implemented storytelling in teaching and learning activities as research subjects. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña (2018) through three main stages: data reduction, data presentation, and drawing conclusions. The results of the study show that teachers apply three main strategies in implementing storytelling: (1) planning strategy, which includes selecting stories according to the theme, learning objectives, and student ability levels; (2) implementation strategy, with the use of expressions, intonation, and supporting media such as images, videos, and gestures to attract students' attention; and (3) evaluation strategies, in the form of retelling activities, discussions, and communication-based performance assessments. Supporting factors for the implementation of storytelling include student enthusiasm and school support, while inhibiting factors include limited time, large student numbers, and variations in language abilities.